Peluang dan Tantangan Perkembangan Tradisi Agama Buddha di Indonesia: Tri Dharma Sebagai Penguat Tradisi dalam Memperkokoh Agama Buddha: Studi Kasus: Vihara Tri Dharma Bumi Raya, Singkawang - Warsito Warsito (Jurnal Budi Pekerti Agama Buddha, 2024)
This research examines the opportunities and challenges in the development of Buddhist traditions in Indonesia, with a specific focus on the role of Tri Dharma (三教 Sam Kauw) as a tradition-strengthening element in fortifying Buddhism in Singkawang City, West Kalimantan. The research is grounded in the dynamic development of Buddhism in Indonesia, which has been influenced by modernity and diverse interpretations of teachings. Utilizing a qualitative descriptive method through observation, interviews, and document analysis with religious leaders and Buddhist adherents in Singkawang City, particularly at the historic Vihara Tri Dharma Bumi Raya (established 1873-1878), the findings reveal that the Tri Dharma tradition—integrating Buddhism (佛教), Confucianism (儒教), and Taoism (道教)—holds significant potential in strengthening religious identity and practices through values of wisdom, virtue, and harmony integrated into daily life. The research identifies key opportunities including strong cultural identity, vibrant ritual traditions (Cap Go Meh festival, Tatung rituals), community support structures, and religious tourism potential. However, challenges include limited deep understanding of Tri Dharma teachings among younger generations, influences of popular culture that erode traditional values, pressures of globalization, and modernization impacts. The research implications emphasize the necessity of systematic efforts in socializing and internalizing Tri Dharma teachings through formal and non-formal education, digital media engagement, youth involvement in Vihara activities, tradition documentation and preservation, and inter-Vihara collaboration to ensure Buddhist traditions continue to develop and strengthen their existence in Indonesia's pluralistic society.